Systematic review and meta-analysis of standard-dose imatinib vs. high-dose imatinib and second generation tyrosine kinase inhibitors for chronic myeloid leukemia - Hoffmann, Verena Sophia; Hehlmann, Rüdiger (Journal of cancer research and clinical oncology, 2017)
Purpose: Most randomized clinical trials evaluating second generation tyrosine kinase inhibitors (TKI) for the first-line treatment of Chronic Myeloid Leukemia used as comparator the ‘standard’ dose of 400 mg imatinib daily. Several studies showed higher rates of major molecular remission (MMR) at 12 months with 800 mg compared to 400 mg, suggesting that high-dose imatinib may be the appropriate comparator rather than 400 mg. Methods: We systematically reviewed randomized trials comparing the two dosages, calculated a common estimator and compared the result to a common estimator of trials evaluating a second generation TKI in comparison with 400 mg imatinib daily. Results: We identified three trials comparing 400-800 mg imatinib resulting in a common relative risk of 1.30 (1.13-1.49) and indicating a significantly higher rate of MMR in patients treated with 800 mg imatinib (p = 0.0003). We identified five trials comparing 400 mg imatinib daily to a second generation TKI. The common relative risk for MMR at 12 months was 1.69 (1.50-1.90, p < 0.0001). Differences in the prognostic profiles precluded a direct comparison of the common efficacy estimates. Conclusions: We conclude that imatinib was probably not licensed at the optimal dose initially. We suggest that in the future, new TKIs are compared with a higher dose of imatinib. In addition, high-dose imatinib should be considered more often for routine clinical decisions based on the characteristics of the individual patient.
Gesehen am 28.05.2018